Immunological Remission as a Basis for Dose Reduction of Immunosuppressors in Autoimmune Hepatitis: Results of Monocenter Surveillance Study - A. O. Bueverov; S. V. Koblov; P. O. Bogomolov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the study: evaluate the role of normalization of humoral immunity to address dose reduction or discontinuation of immunosuppressors in patients with autoimmune hepatitis (AIH).Patients and methods. The data of 47 patients with AIH who received immunosuppressive therapy from April 2001 to August 2023 were analyzed: 10 men (21 %), 37 women (79 %); the average age was 37 (17–66) years. The follow-up period was 10–180 months. Type 1 AIH was diagnosed in 37 patients, type 2 AIH — in 7 patients, seronegative AIH — in 3 patients. The diagnosis was established according to the IAIHG point system. To confirm the diagnosis, a liver biopsy was performed in 17 patients, a histological picture of AIH was detected in all of them. The most used combination was prednisolone and azathioprine — in 25 patients (53.2 %), as well as methylprednisolone and azathioprine — in 8 patients (17 %).Results. In some patients, when the immunosuppressive therapy decreased below the recommended dose, a relapse of the disease developed (Group 1), and in others, remission persisted (Group 2). The concentration of гамма-globulins in patients of Group 1 was 22.5 mg%, in Group 2 — 17.95 mg% (p = 0.00055). IgG level after achieving remission in Group 1 was 1709.7 mg/dL, in Group 2 — 1381.7 mg/dL (p = 0.000001). The terms of ALT normalization in Group 1 were 2.14 months, in Group 2 — 1.47 months (p = 0.037); AST normalization in Group 1 made 2.22 months, in Group 2 — 1.48 months (p = 0.026).Conclusions. Normalization of humoral immunity, as well as rapid normalization of ALT and AST can be considered as markers of maintaining AIH remission when immunosuppressor doses are reduced below standard doses, and in individual patients — the possibility of immunosuppressive therapy withdrawal. This will reduce the risk of adverse events and increase adherence to the therapy. We propose introducing the term “immunological remission” into the clinical lexicon, which, along with biochemical and histological remission, acts as a predictor of persistent remission of AIH.